2010
DOI: 10.1590/s0100-40422010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds from Rosmarinus officinalis L. and Baccharis dracunculifolia DC. Growing in southeast coast of Brazil

Abstract: Recebido em 4/12/08; aceito em 29/7/09; publicado na web em 11/1/10Chemical composition of leaf volatiles of Rosmarinus officinalis and Baccharis dracunculifolia cultured in Southeast of Brazil has been characterized by GC/MS after simultaneous distillation-extraction. The main components in volatiles of these species showed in common α-pinene, myrcene, 1,8 cineole and camphor. Camphor was the major component among volatiles of B. dracunculifolia and R. officinalis with concentrations exceeding 25%. B. dracunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
6
0
7
Order By: Relevance
“…Similar results were presented by Shahwar et al [ 182 ], who reported that the typical aroma of coriander is due to a mixture of different compounds in which decenal and related compounds ( Table 6 ) assume a high preponderance. Several other authors [ 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 ] have reported that the typical aromatic features exhibited by MAPs are a result of a combined effect of several compounds rather than a single compound, as shown by Kizhakkayil and Sasikumar [ 185 ] for ginger. These authors reported that the typical “spicy” and “fresh” aromas exhibited by ginger is due to the simultaneous presence of different compounds such as zingiberene, 6-gingerol, 8-gingerol, 10-gingerol, 6-shogaol, 8-shogaol, geranial, and neral.…”
Section: Plant Volatile Compounds Responsible For Aromatic Featurementioning
confidence: 99%
“…Similar results were presented by Shahwar et al [ 182 ], who reported that the typical aroma of coriander is due to a mixture of different compounds in which decenal and related compounds ( Table 6 ) assume a high preponderance. Several other authors [ 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 ] have reported that the typical aromatic features exhibited by MAPs are a result of a combined effect of several compounds rather than a single compound, as shown by Kizhakkayil and Sasikumar [ 185 ] for ginger. These authors reported that the typical “spicy” and “fresh” aromas exhibited by ginger is due to the simultaneous presence of different compounds such as zingiberene, 6-gingerol, 8-gingerol, 10-gingerol, 6-shogaol, 8-shogaol, geranial, and neral.…”
Section: Plant Volatile Compounds Responsible For Aromatic Featurementioning
confidence: 99%
“…Composição química semelhante a encontrada neste trabalho foi reportada por Boix 50 , que apontaram, dentre os 23 compostos identificados, a cânfora (33, 17 %), 1,8-cineol (14,02 %), verbenona (8,6 %) e pineno (7,0 %) como componentes majoritários do óleo essencial de alecrim. Probst 30 também identificou a cânfora (27,51%) como componente majoritário, sendo seguido do limoneno (21,01 %), mirceno (11,19 %), α-pineno (10,37 %) e βpineno (5,27 %), β-cariofileno (4,60 %), canfeno (3,64 %), verbenona (3,0 %), borneol (2,10 %), γ-terpineno (1,71 %), linalol (1,15 %), α-felandreno (0,21 %); a partir destes valores, é possível observar similaridade com a composição do óleo essencial deste estudo.…”
Section: Figura 2 Cromatograma Do óLeo Essencial De R Officinalis (unclassified
“…Boix et al (2010) encontraram como principais componentes, dos 25 compostos identificados, β-pineno (7,0%), mirceno (9,52%), 1,8 cineol (14,02%), cânfora (33,17%) e verbenona (8,6%). Trabalho realizado por Prins, Kaatz e Gibbons (2006) traz a cânfora, 1,8 cineol, α-pineno e β-mirceno, nessa ordem, como compostos em maior proporção no óleo, resultado semelhante ao encontrado neste trabalho.…”
Section: Avaliação Da Atividade Moduladoraunclassified